FACTOR MORBIDITY OF NEGLECTED TROPICAL DISEASES - Suswita, Elda; Hasyim, Hamzah; Utami, Depi Nopania; Milandiah, Dewi; Putri, Dinda Andini; Putri, Dwi Novrianti; Yanti, Elda; Sari, Elita (Jurnal Kesehatan - STIKes Prima Nusantara, 2021)
Neglected Tropical Diseases (NTDs) causes a decrease in patient activity and productivity and has an impact on the family and surrounding community. In the last few decades, NTDs have begun to receive attention from various countries because even though the fatality number is weak, the morbidity rate is very high. The aim of this research was to establish a literature review on Neglected Tropical Disease. The method used is literature review; uses the Pub med database as the basis for post search, the use of reviewed articles is journals or articles published in the last 10 years with a total of 30 articles. Partnerships linking key donor agencies, charities, NGOs, regulatory authorities, the pharmaceutical industry, and other essential needs managers are vital in fighting NTDs and it is possible to access the healing process for everyone in the world.The potential impacts are universal drawbacks published with the decadent changes in the air, namely in part: dispensation, most notably on vector-borne diseases.The results of data extraction it can be concluded thatNTDs is a neglected disease even though this disease can last a long time and interfere with personal, family and community activities and productivity.